Southeast Asia EAA Archives - EAA Editorial Office (Education About Asia, 2021)
Southeast Asia still seems to garner too little attention in American school and university courses. The following sample archival selections should be useful as student assignments and/or teacher backgrounders. Southeast Asia is Maritime Asia at one level and understanding the Indian Ocean and its role in global history is a good place to start. Most students (and some teachers, including myself two decades ago), have little or no specific understanding of the size and importance of the Indian Ocean.
Keywords: Cambodia; Culture; Education; Indonesia; Philippines; Singapore; Southeast Asia; Vietnam; World History